ESTIMATE OF BONE BIOMARKER ON OSTEOPOROSIS IN IRAQI POSTMENOPAUSAL WOMEN - AlSahib, Zainab qasim Abd; Ali, Muataz Hussein (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Background; Osteoporosis (OP) is a chronic and a progressive disease characterized by low bone mass and micro-architectural deterioration of bone tissue, resulting in an increased risk of fracture .Dual-energy X-ray absorptiometry (DXA) is commonly used for diagnosis of osteoporosis. Bone turnover markers have advantages over DXA, as they are cheap, non-invasive and can detect changes in bone turnover rates earlier. Aims of the study: to investigate the significance of bone turnover biochemical markers; serum parathyroid, serum osteopontin and Vitamin D3 in evaluating osteoporosis for postmenopausal Iraqi women with and without history of vertebral fracture, as well as to explore the relationship of these markers with bone mineral density (BMD). Methodology: Forty-four (85) postmenopausal women were included in this study with age range (45-70years). Subjects were divided into three groups: osteoporosis postmenopausal women: (n=45), osteopenia postmenopausal women: (n=24) and healthy postmenopausal women (n=16) (serve as controls). Patients were diagnosed as osteoporosis and controls as normal by measuring bone mineral density (BMD), using dual energy x-ray absorptiometry (DXA). In addition, serum calcium, phosphorous and alkaline phosphatase measured by spectrophotometer. Result; BMD and T-score were significantly lower in osteoporotic postmenopausal group as compared with healthy group (p=0.009) (p=<0.001). Serum ALP levels were elevated significantly in osteoporotic postmenopausal group as compared with healthy group (p=<0.001). Serum Ca levels and serum PO4 levels were elevated significantly in Healthy postmenopausal group as compared with osteoporotic group (p=0.65) (p=0.957). Conclusions: The levels of ALP in serum could be used as a biochemical indicator in the early diagnosis of osteoporosis postmenopausal women.